2019
DOI: 10.1016/j.heliyon.2019.e02049
|View full text |Cite
|
Sign up to set email alerts
|

Density and viscosity of liquid ZrO2 measured by aerodynamic levitation technique

Abstract: Liquid ZrO 2 is one of the most important materials involved in severe accident analysis of a light-water reactor. Despite its importance, the physical properties of liquid ZrO 2 are scarcely reported. In particular, there are no experimental reports on the viscosity of liquid ZrO 2 . This is mainly due to the technical difficulties involved in the measurement of thermo-physical properties of liquid ZrO 2 , which has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 20 publications
4
35
0
Order By: Relevance
“…In Table 1 the density and thermal expansion coefficient values for liquid oxides measured in this work are listed together with four types of previously published density data: (i) measurements in aerodynamic levitator by Granier and Heurnault’s [ 59 ], Kohara et al [ 65 ], and Kondo et al [ 66 ]; (ii) measurements with the electrostatic levitator on board of International Space Station [ 36 , 37 ]; (iii) refinement from pair distribution function analysis (PDF) of synchrotron X-ray scattering [ 62 ]; (iv) ab initio molecular dynamic computations [ 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 the density and thermal expansion coefficient values for liquid oxides measured in this work are listed together with four types of previously published density data: (i) measurements in aerodynamic levitator by Granier and Heurnault’s [ 59 ], Kohara et al [ 65 ], and Kondo et al [ 66 ]; (ii) measurements with the electrostatic levitator on board of International Space Station [ 36 , 37 ]; (iii) refinement from pair distribution function analysis (PDF) of synchrotron X-ray scattering [ 62 ]; (iv) ab initio molecular dynamic computations [ 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thermophysical properties of liquid metals and their oxides, such as density, surface tension, and viscosity, are significant for industrial applications of these materials and for understanding the structure and order within these liquids. Although the high melting temperatures of liquid metals pose a challenge for contact experiments, the development of levitation technologies, such as electrostatic levitation (ESL) (Paradis et al 2001;Rhim et al 1999;Ishikawa et al 2001), electromagnetic levitation (EML) (Egry et al 1995;Bayazitoglu et al 1998;Seidel 2011;Sauerland et al 1993), and aerodynamic levitation (ADL) (Kargl et al 2015;Langstaff et al 2013;Benmore and Weber 2017;Kondo et al 2019), over the past years has facilitated measurements at high temperatures without contamination. The suitable material for a specific type of levitation technique depends on the operating principle of the levitator.…”
Section: Introductionmentioning
confidence: 99%
“…It increased only from 59.48 to 61.5 wt%. This indicated that the addition of chromium with its low viscosity (5.7 mPa s) 29 compared to that of ZrO 2 (13.0 mPa s) 27 might alter the physicochemical properties of the system, which caused its ease of spreading through solid Nb 6 C 5 granules. To further understand and evaluate the chromium addition effect and explain the experimental results, a set of equilibrium calculations were performed using the thermodynamic computation tool FactSage 7.3™ 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it was expected that this high liquid phase percentage would help in the sintering process 26 and obtaining a high‐density product almost free of pores, which did not happen. This abnormal behavior may be attributed to the high viscosity of the molten zirconia phase (13.0 mPa s) 27 that had to pass through the solid niobium carbide grains. Practically, the time was not enough to either melt or spread the entire amount of ZrO 2 due to the high rate of heat dissipation.…”
Section: Resultsmentioning
confidence: 99%